The Influence of Educators' Tabletop Role-Playing Games Familiarity on the Implementation of LARPs in Adult Education (RPG学研究: Japanese Journal of Analog Role-Playing Game Studies, 2024)
The principal purpose of this study is to investigate the overall attitude of adult trainers in Greece about educational live-action role-playing games (edu-LARPs) and their utilization as a teaching method. More specifically, it is an attempt to determine if the trainers’ experience with various tabletop role-playing games affects their attitude towards this method and the frequency of usage. Moreover, the ultimate goal is to be an introduction to a large portion of this particular educational community with this innovative teaching method, setting the ground for further research that will help expand the academic field.The results depict a statistically significant correlation between the overall attitude of the trainers towards edu-LARPs and their level of experience with tabletop RPGs. This correlation seems to extend also to the frequency of usage.